STRATEGI MENINGKATKAN JUMLAH MAHASISWA MENGGUNAKAN ANALISIS BAURAN PEMASARAN - Lestari, Ari (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Education is a form of conscious and systematically planned activity in realizing an atmosphere of continuous learning and learning process and actively developing one's potential to have spiritual strength, self-management, intelligent personality, noble character and soft skills and hard skills needed by oneself, society and state. The problem faced by the College of Informatics and Computer Logic Management is that the target of accepting students in 2019-2022 is not achieved. So if no concrete action is taken, it is feared that it will impact on this High School. This study aims to formulate policies and alternative strategies based on the marketing mix to improve the decision to choose a College of Logic in the future. The free variables studied are derivative variables of the marketing mix strategy: Products (Curriculum), Education Costs, Location, Promotions, People (Teaching Staff and Education Personnel), Processes and Services. As for the bound variable, namely the Decision to Choose.